2018
DOI: 10.3390/pharmaceutics10040231
|View full text |Cite
|
Sign up to set email alerts
|

Solid Lipid Nanoparticles for Dibucaine Sustained Release

Abstract: Dibucaine (DBC) is among the more potent long-acting local anesthetics (LA), and it is also one of the most toxic. Over the last decades, solid lipid nanoparticles (SLN) have been developed as promising carriers for drug delivery. In this study, SLN formulations were prepared with the aim of prolonging DBC release and reducing its toxicity. To this end, SLN composed of two different lipid matrices and prepared by two different hot-emulsion techniques (high-pressure procedure and sonication) were compared. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 50 publications
5
25
0
Order By: Relevance
“…The three types of NLC formulations developed in this study showed very good capacity to carry TTC, with %EE values ranging from 63.7 to 68.1% and %DL > 11 (Table 2 ), reflecting the strong partition of the non-ionized form of TTC in the lipid milieu 43 . Indeed, the encapsulation efficiency determined for TTC in these nanoparticles was in the range of those reported (> 55%) for other hydrophobic local anesthetics such as dibucaine, bupivacaine and ropivacaine 16 , 44 , 45 and higher (< 37%) than those observed in NLC with more hydrophilic agents such as lidocaine and prilocaine 8 . The drug loading capacity is another parameter that expresses the upload capacity of DDS (Eq.…”
Section: Resultsmentioning
confidence: 47%
“…The three types of NLC formulations developed in this study showed very good capacity to carry TTC, with %EE values ranging from 63.7 to 68.1% and %DL > 11 (Table 2 ), reflecting the strong partition of the non-ionized form of TTC in the lipid milieu 43 . Indeed, the encapsulation efficiency determined for TTC in these nanoparticles was in the range of those reported (> 55%) for other hydrophobic local anesthetics such as dibucaine, bupivacaine and ropivacaine 16 , 44 , 45 and higher (< 37%) than those observed in NLC with more hydrophilic agents such as lidocaine and prilocaine 8 . The drug loading capacity is another parameter that expresses the upload capacity of DDS (Eq.…”
Section: Resultsmentioning
confidence: 47%
“…The thermogram of CP and NPX exhibited a single endothermic peak at 55 °C and 157 °C, respectively, corresponding to their melting points 10,21 . For the NLC and NLC-NPX formulations a single endothermic transition was detected at 52 °C, related to the melting point of cetyl palmitate 22 .…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, calorimetric measurements revealed thermodynamic features of NLC-NPX formulation. The lower transition observed for the residual CP peak probably results from its interaction with the liquid lipids, decreasing the crystallinity of the nanoparticles core 22,40 . Moreover, the lack of the endothermic transition assigned for NPX in the NLC-NPX sample can be a sign of the solubilization of the NSAID in the nanoparticles (as pictured by the NTA data – Table S6).…”
Section: Discussionmentioning
confidence: 95%
“…The long-term stability study is an essential test to ensure the shelf-life of novel formulations ( Barbosa et al., 2018 ). Then, the nanoparticle size (nm), PDI (particle size distribution), and Zeta potential (mV) values were followed over a year at 25°C ( Rodrigues da Silva et al., 2017 ).…”
Section: Discussionmentioning
confidence: 99%